Gil Mandelzis and Traiana : value is in the eye of the beholder - Shefsky, Lloyd E., (SAGE knowledge. Cases., 2016)
This case focuses on the career of Gil Mandelzis, a former Wall Street investment banker who recognized and seized an opportunity to build his company, Traiana, into a successful services provider for financial institutions in the foreign exchange prime brokerage market. The case describes Mandelzis's history, beginning with his earliest entrepreneurial effort as a Tel Aviv bar owner and continuing through his decision to start Traiana.